Access to Mental Health Services for Children in Balochistan - Khan, Hazrat Ali; Ashraf, Sohail; Hasni, Lalzadi; Anwar, Mohammad; Khalid, Sahibzada Abdul; Sulaiman, Muhammad; Ullah, Amin; Kakar, Sana Ullah (Biological and Clinical Sciences Research Journal, 2025)
Access to mental health services for children in Balochistan, Pakistan, remains critically limited, despite a growing global and national recognition of child and adolescent mental health as a fundamental component of public health. Balochistan, Pakistan's largest and least developed province, faces acute challenges including poverty, insecurity, poor infrastructure, and lack of specialized human resources—factors that have led to a severe gap in both the availability and accessibility of mental health care, especially for vulnerable populations such as children. This study aims to explore the scope and limitations of mental health services available to children across Balochistan, assess the implementation of policies following the provincial Mental Health Act of 2019, and evaluate recent efforts by public and non-governmental institutions to address this gap. The research methodology is based on a qualitative review of secondary sources, including government reports, WHO assessments, NGO project evaluations, and academic literature. Findings reveal that services are highly centralized in Quetta, with rural districts having little or no access to trained child psychologists or psychiatrists. Infrastructure gaps, lack of funding, social stigma, and low awareness among caregivers further exacerbate the treatment gap. While some initiatives—such as school-based trauma programs, mental health integration into basic health units, and community outreach—show promising results, their scale remains limited and unsustainable without systemic reform. The study concludes that meaningful progress requires a multipronged strategy: decentralizing mental health services, training non-specialist health workers in child mental health, integrating mental health education into schools, enforcing mental health policy frameworks, and increasing budget allocations. These measures can collectively strengthen the province’s capacity to provide accessible, equitable, and child-friendly mental health services.